2012
DOI: 10.1093/toxsci/kfs163
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates Stimulate the Epithelial to Mesenchymal TransitionThrough an HDAC6-Dependent Mechanism in Human BreastEpithelial Stem Cells

Abstract: Phthalates are environmental hormone-like molecules that are associated with breast cancer risk and are involved in metastasis, a process that requires the epithelial-mesenchymal transition (EMT). However, few studies have addressed the potential effects of phthalates on stem cells. Here we tested the hypothesis that phthalates such as butyl benzyl phthalate and di-n-butyl phthalate induce EMT in R2d cells, a stem cell-derived human breast epithelial cell line that is responsive to estradiol for tumor developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…We and others have shown that phthalate exposure results in pronounced cell transformation, both in vitro and in tumor xenograft models [30]. In the current study, we show that the BBP-LEF1 cascade observed in R2d cells can be recapitulated in the ER-positive breast cancer cell line MCF-7.…”
Section: Discussionsupporting
confidence: 69%
“…We and others have shown that phthalate exposure results in pronounced cell transformation, both in vitro and in tumor xenograft models [30]. In the current study, we show that the BBP-LEF1 cascade observed in R2d cells can be recapitulated in the ER-positive breast cancer cell line MCF-7.…”
Section: Discussionsupporting
confidence: 69%
“…It is worth noting that some of these networks seem to be regulatory keys of therapeutic resistance, such as Survivin [37], Topoisomerase II α [38], Desmoglein 2 [39], BCL2-interacting killer [40], and ribonucleotide reductase M2 polypeptide [41]. In addition, several identified proteins have a role in CSC self-renewal, which has been demonstrated in the cases of maternal embryonic leucine zipper kinase [42], transcription factor AP-2 γ [43], the microtubule associated TPX2 protein [44], and Aurora kinase A [44]. At present, our efforts are focused on the characterization of some of these targets and our final goal is the setup of new DNA vaccines that will be tested in BALB-neuT mice in association with anti-HER2 vaccination, in order to improve the vaccination's efficacy against advanced tumor and metastases.…”
Section: The Urgency Of Defining the Most Promising Tme-associatedmentioning
confidence: 99%
“…2,3 Ortho-phthalates are known to stimulate the epithelial-tomesenchymal transition necessary for cancer invasion and metastasis, mediated by histone deacetylase 6. 4 In vitro studies support a role of phthalates in mechanisms of colon carcinogenesis. Additionally, a dose-dependent effect of ortho-phthalates on aryl hydrocarbon receptor (AhR) function has been suggested.…”
Section: Introductionmentioning
confidence: 96%
“…Ortho‐phthalates are known to stimulate the epithelial‐to‐mesenchymal transition necessary for cancer invasion and metastasis, mediated by histone deacetylase 6 . In vitro studies support a role of phthalates in mechanisms of colon carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%